Photo-induced energy transfer relay of N-heterocyclic carbene catalysis: an asymmetric α-fluorination/isomerization cascade. Issue 6 (21st December 2020) - Jiang, Xinhang; Li, En; Chen, Jiean; Huang, Yong
Abstract : The geometric configuration of olefin products is often driven by thermodynamic control in synthesis. Abstract : The geometric configuration of olefin products is often driven by thermodynamic control in synthesis. Methods enabling switching of cis / trans selectivity are rare. Recently, photosensitized approaches have emerged as a powerful tool for accomplishing this task. In this report, we report an in situ isomerization of an N-heterocyclic carbene (NHC)-bound intermediate by a photo-induced energy transfer process that leads to selective access of chiral allylic fluorides with a cis -olefin geometry. In the absence of a photocatalyst or light, the reaction proceeds smoothly to give ( E )-olefin products, while the ( Z )-isomer can be obtained under photosensitizing conditions. Preliminary mechanistic experiments suggest that an energy transfer process might be operative.